Development of android-based educational games about the domain of educational technology - Moscato, Jason (Pandawan Sejahtera Indonesia, 2023)
This research aims to produce an Android game product containing TP Domain material that is feasible as an alternative learning media for Raharja University students. The feasibility value is known through expert assessment, potential users, and learning usability. Product development was carried out through five main stages: preliminary study, planning, design, development, and evaluation. Data collection was carried out by preliminary study interviews, learning style identification, expert validation, potential user validation, and experimental testing. The number of respondents consisted of one lecturer, two media and material experts, and 60 students. The results showed that the developed product has met the eligibility criteria of media validation, material, prospective users, and usability testing. The material expert's assessment falls into the very feasible category, while media experts and prospective users fall into the feasible category. The product is also proven to have usability based on the difference in the average pretest and posttest scores of the two test groups, so that the comparison of the gain values shows a significant difference